1997
DOI: 10.1002/(sici)1097-0134(199708)28:4<481::aid-prot3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of NMR relaxation experiments and MD simulations for characterizing protein dynamics

Abstract: Model-free parameters obtained from nuclear magnetic resonance (NMR) relaxation experiments and molecular dynamics (MD) simulations commonly are used to describe the intramolecular dynamical properties of proteins. To assess the relative accuracy and precision of experimental and simulated model-free parameters, three independent data sets derived from backbone 15N NMR relaxation experiments and two independent data sets derived from MD simulations of Escherichia-coli ribonuclease HI are compared. The widths o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 52 publications
(109 reference statements)
7
41
0
Order By: Relevance
“…Difficulties in controlling for differences in the models used to fit experimental data is a confounding factor in attempts to determine absolute accuracy of experimental values of S 2 [21]; consequently, whether further improvements in prediction accuracy are limited by the quality of the experimental S 2 data or merely by the size of the feature set that can be stably parameterized is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in controlling for differences in the models used to fit experimental data is a confounding factor in attempts to determine absolute accuracy of experimental values of S 2 [21]; consequently, whether further improvements in prediction accuracy are limited by the quality of the experimental S 2 data or merely by the size of the feature set that can be stably parameterized is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Ratios less than one for the AMBER99 simulations are consistent with a body of literature reporting that MD trajectories based on this and similar force fields often underestimate S 2 in loop regions. 1,10,[14][15][16]52 The trajectories using the two force fields exhibit differences in their internal motional correlation times, and therefore the total length of the trajectory, T MD , required to produce optimal agreement with experimental S 2 values is different for the two force fields. To demonstrate this effect, the order parameters were computed from the AMBER99 and AMBER99SB trajectories after 500 ps and 1, 5, 10, and 20 ns and compared against the experimental values ( Table 2).…”
Section: Comparison Of Calculated Order Parameters With Experimentmentioning
confidence: 99%
“…Comparisons of MD simulations [6][7][8][9][10][11][12][13][14][15][16] with NMR relaxation data typically focus on the generalized N-H S 2 order parameter by Lipari and Szabo. 17,18 S 2 is a measure of the spatial restriction of the N-H vector in a molecule-fixed frame that takes values between 0 (large amounts of motion) and 1 (no motion) and which can be extracted from longitudinal T 1 , transverse T 2 , and heteronuclear Overhauser effect (NOE) data.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of three experimental sets of 15 N relaxation parameters along with two theoretical sets calculated from molecular dynamics simulations showed [301] that the NMR and MD generalized parameters are of comparable accuracy for residues exhibiting motions on a fast timescale. The comparison of the conformational entropy and the NMR order parameters on native and denatured staphylococcal nuclease [302] revealed that the general behavior of the experimental order parameters between native and unfolded states was reproduced by the simulations, but that the majority of theoretical order parameters disagree with the corresponding experimental ones.…”
Section: Molecular Dynamics and Ensemble Refinementmentioning
confidence: 99%